The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1959
DOI: 10.5962/bhl.title.7363
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic keys to plant, soil and aquatic nematodes [by] Bruce E. Hopper and Eldon J. Cairns.

Abstract: A few consolidated sources of descriptions and illustrations of plant and soil forms, in particular, are available and should be used along with the taxonomic keys. At best, keys are only attempted short cuts to" the recognition of certain specimens. In all cases check the decisions by referral to descriptions and illustrations of the nematodes. There are some excellent volumes available to workers who do not have access to the necessarily large reprint files of the taxonomist. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Identification of different subpopulations of MiP has been reported by others [ll]. Hence, Hopper and Cahill [6] showed that the bactericidal and tumoricidal functions of MiP can be dissociated from production of PGEz and IL1 and that these functions are related to different subsets of cells, separable by velocity sedimentation. Using the BSA gradient method, other investigators have found two major subpopulations of peritoneal MQ.…”
Section: Discussionmentioning
confidence: 73%
“…Identification of different subpopulations of MiP has been reported by others [ll]. Hence, Hopper and Cahill [6] showed that the bactericidal and tumoricidal functions of MiP can be dissociated from production of PGEz and IL1 and that these functions are related to different subsets of cells, separable by velocity sedimentation. Using the BSA gradient method, other investigators have found two major subpopulations of peritoneal MQ.…”
Section: Discussionmentioning
confidence: 73%
“…Also, Thorne (1939) added two other genera to this subfamily, namely Oionchus Cobb, 1913 and Enoplocheilus Kreis, 1932. Leaving aside S. rotundicauda Goodey, 1951, no other new Sectonema species was described during the two next decades, 40s and 50s, and the taxonomical status of the genus did not suffer any significant change in the subsequent classification systems proposed for nygolaims (Baker, 1962;Clark, 1961;Goodey, 1951Goodey, , 1963Hopper & Cairns, 1959;Jairajpuri, 1964;Meyl, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…The cell-free system we have developed functions with high fidelity as far as can be judged from the examination of the products synthesized under the direction of phage T, DNA: not only can many early gene products such as RNA polymerase (gene 1; Mr 100 000) a DNA ligase (gene 1.3; Mr 40 000) and the gene 0.3 product (M, 8700) be identified on the basis of their mobility in SDS-acrylamide gels (Plate 1; [ 131, but bands corresponding to many late products are also present. In this respect, the system compares well with the in vivo situation and with in vitro systems as described previously by Hopper et al [18]. It is interesting to note, however, that whereas other authors [ 19,201 have reported significant synthesis in vitro of the late gene product, lysozyme, the present system like that of Q'Farrell and Gold [lo], gives neither material banding in SDS-acrylamide gels at a position expected for lysozyme, nor a significant amount of enzymically-active protein (data not shown).…”
Section: Discussionmentioning
confidence: 66%